Nurse Staffing and 30-day Readmission of Chronic Obstructive Pulmonary Disease Patients: A 10-year Retrospective Study of Patient Hospitalization - Seung Ju Kim, RN; Eun-Cheol Park, MD, PhD; Kyu-Tae Han, BHM; Sun Jung Kim, PhD; Tae Hyun Kim, PhD (Elsevier, 2016)
Purpose: Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity in many countries, and it has high rate of hospital readmissions due to recurrent exacerbations of the disease. Many previous studies have suggested further examination of the factors that contribute to hospital readmissions of COPD patients. However, evidence on the effects of nurse staffing by registered nurses (RNs) on the readmission of COPD patients is lacking in Korea. The aim of our study was to evaluate the effects of nurse staffing on hospital readmissions of COPD patients. Methods: We used National Health Insurance claim data from 2002 to 2012. A total of 1,070 hospitals and 339,379 hospitalization cases were included in the analysis. We divided the number of RNs per 100 beds and the proportion of RNs on staff to one of three groups (Q1: low; Q2: moderate; Q3: high). A generalized estimating equation model was used to evaluate the associations between readmission and nurse staffing. Results: A higher number of RNs was associated with lower readmission rates of 8.9% (Q2) and 7.9% (Q3) respectively. A similar effect was observed as the proportion of RNs among the total nursing staff gradually increased, resulting in lower readmission rates of 7.7% (Q2) and 8.3% (Q3). Conclusions: Our results suggest notable positive effects of nurse staffing by RNs on patient outcomes. In addition, the magnitude of impact differed between different sizes of hospitals. Thus, human resource planning to solve staffing shortages should carefully consider the qualitative aspects of the nursing staff composition.